Development Of Project-Based Learning Modules For Concentration Subjects In The Visual Communication Design Department - Dena Safitri; Muhammad Yusuf Mappeasse; Sanatang (PT. Global Research Collaboration, 2026)
This study aims to develop a Project Based Learning (PBL) module for specialized subjects in the Visual Communication Design Department at SMK Negeri 7 Pinrang. The research method used is Research and Development (R&D). The module development process was carried out in several stages, including learning needs analysis, planning, design, development, implementation, and evaluation. The learning needs analysis stage involved collecting data on student learning needs, learning objectives, and subject characteristics. The learning module was developed using the Project Based Learning approach, which encourages students to actively learn through practical projects relevant to their expertise in the field of Visual Communication Design. This study used a questionnaire instrument to assess the feasibility of the learning module for the concentration of expertise, which was compiled using a Likert scale. Data were obtained through observation, interviews, documentation, and questionnaires. The results showed that the module for the concentration of expertise subject received an average rating of 94% in the “very feasible” category from subject matter experts and media experts, with a score of 95% in the “very feasible” category. Based on this data, it can be concluded that the concentration expertise module in the Visual Communication Design Department is acceptable for use as a learning medium for students at SMK Negeri 7 Pinrang